Toxicity profile of combined immune checkpoint inhibitors and thoracic radiotherapy in esophageal cancer: A meta-analysis and systematic review - Xu, Tongzhen; Liu, Yunsong; Lu, Xiaotong; Liang, Jun (Frontiers in Immunology, 2022)
Background: Therapies based on the combination of immune checkpoint inhibitors (ICIs) and thoracic radiotherapy (TRT) are transforming the treatment landscape of esophageal cancer. Nevertheless, the available data on adverse events (AEs) mainly stemmed from several prospective clinical trials and retrospective studies, in which, AE data are often handled and reported with less rigor than the primary beneficial outcomes of the study. Thus, we conducted a systematic review to investigate the toxicity spectrum of these novel regimens. Method: We searched for all prospective clinical trials investigating the role of ICIs combined with TRT published between January 2010 and August 2022. Study articles and conference proceedings involving esophageal cancers and reporting the overall incidence or details of treatment-related AEs (trAEs) were synthesized to determine the toxicity profile of combination treatment. We compared trAEs between programmed cell death 1 (PD-1) and programmed cell death ligand 1 (PD-L1) inhibitors, and between sequential and concurrent administration of ICIs and TRT to identify potentially high-risk patients. Results: We obtained toxicity data from 14 clinical trials involving 863 patients. The pooled overall incidence was 88.97% for any-grade trAEs and 18.48% for high-grade trAEs. The three most frequent non-hematologic any-grade trAEs were reactive cutaneous capillary endothelial proliferation (RCCEP, 63.80%), esophagitis (51.54%), and fatigue (33.63%). Meanwhile, RCCEP (15.69%) was the most common non-hematologic high-grade trAE, followed by nausea (4.91%) and anorexia (3.81%). The occurrence rates of any-grade and high-grade pneumonitis were 10.82% and 0.66%, respectively. In subgroup analysis, the toxicity profiles of PD-1 and PD-L1 inhibitors were mostly similar, except for any-grade pneumonitis (15.20% vs 4.88%, p=0.03) and high-grade leukopenia (6.25% vs 59.09%, p=0.00). In addition, concurrent treatment seemed to have a higher incidence of any-grade trAEs (95.20% vs 70.85%, p=0.03) compared with sequential treatment. Conclusion: Our study is the first systematic review to provide a toxicity profile of trAEs in esophageal cancer patients who received ICIs combined with TRT. Most AEs of this combination treatment are tolerable, although the incidence of any-grade trAEs was higher in the concurrent group. The difference in any-grade pneumonitis between PD-1 and PD-L1 inhibitor groups needs further validation in a large clinical trial.